Establishment and follow-up of bifidobacterial species in the gut of healthy bottle-fed infants of 1-4 months age - Mullié, C; Romond, M B; Izard, D (Folia microbiologica, 2006)
Twenty-one healthy bottle-fed infants were screened monthly (1-4 months) for bifidobacteria in their stools. Bifidobacteria were detected by culture and isolates specified by PCR. Alternatively, direct PCR in undiluted fecal suspensions was carried out for detection of bifidobacteria under the cultural detection level. All infants harbored cultivable bifidobacteria throughout the study period. Beerens medium was shown to permit a better recovery of bifidobacteria than MRS and horse blood Columbia agar. Direct PCR detection proved valuable in detecting species for which no cultural isolate could be recovered since the species were under the cultural detection level. B. bifidum, B. longum-infantis and B. breve were confirmed as dominant and stable species in infant stools while B. adolescentis and B. catenulatum group exhibited unstable colonization profiles. A trend towards B. breve decrease began at month 3 while carriage of the B. catenulatum group and B. adolescentis was rising. This observation warrants further analysis to assess a possible switch occurring at month 3 in bottle-fed infants, between so-called infant and adult bifidobacterial species.
Keywords: krmení lahví; Feces; střeva; Culture Media; polymerázová řetězová reakce; kultivační média; Infant; Time Factors; DNA, Bacterial; DNA bakterií; lidé; Humans; Bifidobacterium; kojenec; časové faktory; Bottle Feeding; Polymerase Chain Reaction; Intestines; feces